1976
DOI: 10.1139/f76-249
|View full text |Cite
|
Sign up to set email alerts
|

Community and Species Responses of Chironomidae (Diptera) to Contamination of Fresh Waters by Crude Oil and Petroleum Products, with Special Reference to the Trail River, Northwest Territories

Abstract: RosrNsEnc, D. M., aNo A. P. Wrrns. 1976. Cornmunity and species responses of Chironomidae (Diptera) to contamination offresh waters by crude oil and petroleum products, rvith special reference to the Trail River, Northwest Territolies. J. Fish. Res. Board Can. 33: 1955-1963.On oiled and unoiled arlificial substrates in the Trail River, Norlhwest Territories, communities of Chironomidae were different durinlg open-water periods but were similar over the winter. Greater numbers ofspecies and individuals ofOrtho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
1
17
1
2
Order By: Relevance
“…There are some similarities but also some differences in apparent effects of oil between our study and those of Snow and Rosenberg (1975) and Rosenberg and Wiens (1976). Similarities are that effects seemed to be more severe in shallower habitats, and that Tanytarsini were affected negatively while Orthocladiinae increased following oil treatment.…”
Section: Apparent Effects Of Oil On Insectssupporting
confidence: 73%
See 1 more Smart Citation
“…There are some similarities but also some differences in apparent effects of oil between our study and those of Snow and Rosenberg (1975) and Rosenberg and Wiens (1976). Similarities are that effects seemed to be more severe in shallower habitats, and that Tanytarsini were affected negatively while Orthocladiinae increased following oil treatment.…”
Section: Apparent Effects Of Oil On Insectssupporting
confidence: 73%
“…McCauley (1966) saw a change in benthic composition, primarily elimination of the predators Agrion (Odonata) and Dugesia (Turbellaria) and the omnivore Gammarus (Amphipoda) from stretches of a stream with oily sediments, whereas deposit-feeding Tubifex (Oligochaeta), Chironomus, Nematoda and predaceous Hirudinea persisted. Rosenberg and Wiens (1976) divided species responses in experimental oil spills into categories of negative, positive and indifferent, and showed that different species of Chironomidae occurred in each category. Similarly, spills in Mackenzie Delta lakes affected certain chironomids more than other chironomids and oligochaetes (Snow and Rosenberg, 1975).…”
Section: Apparent Effects Of Oil On Insectsmentioning
confidence: 99%
“…In fact, insects in the order Diptera are considered to be very tolerant of pollutants and some taxa show a positive correlation with the presence of oil (Rych and Duchrow, 1973;Rosenberg and Wiens, 1976;Woodward and Riley, 1983). Rosenberg and Wiens (1976) investigated the abundance of two species of Cricotopus on artificial substrates in the presence and absence of oil, and both species were more abundant on substrates with oil.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenberg and Wiens (1976) investigated the abundance of two species of Cricotopus on artificial substrates in the presence and absence of oil, and both species were more abundant on substrates with oil. In one case an intermediate concentration of crude oil was responsible for the greatest increase in the abundance of Chironomidae (Cushman and Goyert, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation